Developing and validating the Japanese version of professional attitude scale for nurses. (12th October 2020) - Takada, N.; Asakura, K.; Sugiyama, S.
Abstract : Aim: We developed and psychometrically tested the Japanese version of the Professional Attitude Scale for Nurses (PASN‐J). Background: Nurses must recognize the importance of their professionalism; therefore, it is critical to quantitatively measure nurses' professional attitudes. Introduction: This instrument validation study was designed to generate an itemized scale and examine its content validity/psychometric testing using a sample of Japanese nurses. Methods: Based on a trait approach focusing on the characteristic traits of the nursing profession, a 59‐item draft scale was generated. During November 2017, 2657 nurses from 29 facilities in Japan were surveyed. The questionnaire included demographics, the 59‐item draft scale, and a self‐report scale of nurses' professional behaviour and nursing practice ability. Using exploratory and confirmatory factor analyses, we evaluated the construct, criterion‐related, concurrent, and known‐groups validity, and reliability of the PASN‐J. Results: Data from 1716 participants were analysed. The analyses yielded a 38‐item, 3‐factor scale that adequately fit the data. PASN‐J scores were positively correlated with nurses' professional behaviour and nursing practice ability. Conclusion: The 38‐item PASN‐J has good reliability and validity, making it useful for measuring the current condition of nursing professionalism and evaluating nursing education. Implications for Nursing and Health Policy: This scale can evaluate nursing education and promote nurses' professionalism. The PASN‐J will help identifying the elements of undergraduate nursing education that require further emphasis. Additionally, the PASN‐J could facilitate the development of nursing policies to promote professional development in nurses. Ultimately, evaluating nursing education with the PASN‐J enhances nurses' professional attitudes and subsequently improves their quality of nursing, nursing efficiency and patient outcomes.